Analysis of the Influence of Socio-Economic and Demographic Factors on Patients’ Perception of Health Service Quality at Amanah Bunda Medika Cilnic in the Digital Era - Lyliana Endang Setianingsih; Ice Marini; Emmelia Kristina Hutagaol (Jurnal EduHealth, 2023)
Amanah Bunda Medika Clinic is a private clinic in Bekasi Regency, West Java, which provides health services such as midwifery, general polyclinic, and dental polyclinic. Based on interviews conducted with clinic owners, they have not yet conduct patient satisfaction survey. Therefore, it is important to consider collecting data regarding the perceptions of patients and their families, to find out how the public views the quality of health services provided by the Amanah Bunda Medika Clinic, especially in relation to the digital era in the health service sector. The aim of this study is to determine the influence of socioeconomic and demographic factors on patient perceptions of health service quality at Amanah Bunda Medika Clinic in the digital era. The method used is mixed methods. Quantitative research was carried out using univariate, bivariate and multivariate analysis. The subjects of this research are Amanah Bunda Medika Clinic patients. Qualitative research was carried out through in-depth interviews with the healthcare provider of Amanah Bunda Medika Clinic. The results of bivariate analysis showed that the factors of profession and family income did not have a significant relationship with the patient's perception of health service quality with p-value > 0.05, while the factors of age, gender and level of education were significantly related to the patient's perception of health service quality with p-value < 0.05. In the multivariate analysis stage, the most influential factor is age, with odd ratio value of 4.203, which means the older the respondent, the bigger the chance of having a very good perception of health service quality, while the factors of gender and education level had a negative relationship with odd ratio value less than 1, which means that women have a lower perception of health service quality than men, and patients with higher education have lower perception of health service quality than patients with primary – secondary education. The results of interviews with the healthcare provider indicated that patients were unfamiliar with the concept of patient perception surveys, and this could be overcome by socializing the benefits of surveys to improve service quality.